PENGARUH PEMANFAATAN INTERNET TERHADAP KEBERDAYAAN PETANI PADI SAWAH DI KELURAHAN LAMERORO KECAMATAN RUMBIA KABUPATEN BOMBANA - Rambakila, Meyrama Pau'; Rela, Iskandar Zainudin; Wunawarsih, Ima Astuty (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
Rice paddies play a strategic role in Indonesia's food security and economy, especially in Bombana Regency. However, the increase in production has not been accompanied by a corresponding increase in farmer empowerment. Consequently, the use of the internet is regarded as a crucial factor in enhancing farmers' access to information, capacity, and independence. The objective of this study is to analyze the impact of internet utilization on the empowerment of rice farmers in Lameroro Village, Rumbia District, Bombana Regency. The present study employs a quantitative approach, utilizing a survey design. The study population consists of all rice farmers who use the internet in their farming activities in Lameroro Village, with a total of 331 individuals grouped into 11 farmer groups. The sample size was determined using the Slovin formula with a margin of error of 10%, resulting in a sample of 77 respondents. The data collection process entailed the implementation of a survey method, encompassing the administration of questionnaires, the conduction of interviews, the meticulous analysis of documentation, and a thorough literature study. The independent variables in this study were internet usage and farmer empowerment. The research data was then subjected to analysis using both descriptive and inferential statistical methods with the assistance of SPSS software. The results showed that internet use had a positive and significant effect on the empowerment of rice farmers in Lameroro Village. Internet use by rice farmers was maximized, especially for accessing technical information on cultivation, market prices, pest and disease control, and weather forecasts. The high intensity and sustainability of internet use reflect farmers' ability to adapt to digital technology as a strategic source of information in making farming decisions. The empowerment of rice farmers has been carried out well, as reflected in their increased awareness to change, ability to improve capacity, resilience in facing obstacles, and ability to cooperate and show solidarity. The regression analysis results show that internet use explains 37.0% of the variation in farmer empowerment, while the rest is influenced by other factors such as institutional support, training, and infrastructure.